METHODOLOGICAL DESCRIPTION OF TOOLS FOR DEVELOPING STUDENTS’ WRITING SKILLS IN THE CONTEXT OF DIGITALIZATION - Muydinov Mansurjon Ilhomhon o‘g‘li (TADQIQOTLAR, 2025)
ABSTRACT: This article investigates the methodological principles and tools that support the development of students’ writing skills in the digital era. It focuses on the pedagogical potential of artificial intelligence, digital learning platforms, and multimodal environments in enhancing linguistic, communicative, and creative competencies. The study emphasizes that integrating technological innovations into writing instruction not only enriches language learning but also fosters autonomy, collaboration, and critical thinking.